2021
DOI: 10.1155/2021/6699028
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antidepressants among Patients Diagnosed with Depression: A Scoping Review

Abstract: Introduction. Depression is a major global health problem with a relatively high lifetime prevalence and significant disability. Antidepressants are the most effective medications used for the treatment of depression. Hence, this study is aimed at summarizing the studies on antidepressant use among patients diagnosed with depression. Method. PubMed, Embase, Web of Science, Scopus, and Google Scholar were searched for literature (2000-2019) using keywords such as depression, drug utilization, antidepressants, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The World Health Organization has reported that more than 264 million people of all ages suffer from depression globally (GBD 2017 Disease and Injury Incidence and Prevalence Collaborators, 2018). Selective serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, tricyclic antidepressants, monoamine oxidase inhibitors and some atypical agents are the antidepressant drug groups used in the treatment of depressive disorders today (Marasine et al, 2021). However, a significant proportion of patients with depression either does not respond adequately to these drugs or cannot tolerate various drug-induced side effects (Papp et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization has reported that more than 264 million people of all ages suffer from depression globally (GBD 2017 Disease and Injury Incidence and Prevalence Collaborators, 2018). Selective serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, tricyclic antidepressants, monoamine oxidase inhibitors and some atypical agents are the antidepressant drug groups used in the treatment of depressive disorders today (Marasine et al, 2021). However, a significant proportion of patients with depression either does not respond adequately to these drugs or cannot tolerate various drug-induced side effects (Papp et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…SSRIs are still preferred among antidepressant categories. 6 The serotonergic system is highly complex with diverse signaling networks. Serotonin neurotransmitters able to activate the largest number of receptor subtypes and modulates an increasing number of physiological functions such as anxiety, mood, cognition, sleep, and appetite.…”
Section: Introductionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors (SSRIs) act on the serotonin transporter (SERT), are the most used among depressive patients, and are also prescribed for anxiety disorders. SSRIs are still preferred among antidepressant categories …”
Section: Introductionmentioning
confidence: 99%
“…It has been widely acknowledged that it takes about at least 6–8 weeks for antidepressants to unfold their action entirely ( 5 ). According to the FDA, SSRIs can increase the risk of suicide in the first 2 weeks of treatment ( 6 ). Besides, it is still controversial that medications have side effects such as weight gain/loss, insomnia, and loss of appetite in treating adolescent depression ( 7 ).…”
Section: Introductionmentioning
confidence: 99%